Why Do Freshwater Turtles Aggregate at Basking Sites? - Fenech, Malcolm (Université d'Ottawa / University of Ottawa, 2023)
Many animals, including reptiles, aggregate for asocial reasons, social reasons, or both. Freshwater turtles aggregate at basking sites, but it remains unclear why they do so. Previous studies have suggested basking aggregations may occur at basking sites that have preferred habitat characteristics, or because aggregation increases the detection of predators. I tested these two hypotheses with painted turtles (Chrysemys picta) and northern map turtles (Graptemys geographica), two locally abundant species that aggregate at basking sites at Petrie Island, Ottawa, Ontario, Canada. I predicted that basking sites with larger aggregations of basking turtles should have more available basking area, more open canopy, and be further from the shoreline. I also predicted that turtles in larger basking aggregations should escape into the water from further away than turtles in smaller basking aggregations when approached by a potential predator. I conducted basking surveys in 2021, where I photographed basking turtles and measured basking site characteristics at each available basking site. I conducted disturbance trials in 2022, where I measured the flight initiation distance of basking turtles. I found that painted turtles aggregated at basking sites with more available basking area and a south-facing orientation while northern map turtles aggregated at basking sites with more available basking area and further away from the shoreline. I also found that painted turtles and northern map turtles fled basking sites from further away when basking in larger groups. The biological effects of basking site characteristics on the number of basking turtles were small, and so were those of the number of basking turtles on flight initiation distance, suggesting there may be additional reasons why freshwater turtles aggregate at basking sites.
Keywords: Aggregation; Basking; Behaviour